Local Anesthetic Systemic Toxicity After Thoracal Paravertebral, Pectoralis I, and Serratus Anterior Plane Block in Modified Radical Mastectomy - Pranuri, Gesit Entra; Sudadi, Sudadi; Rachman, Farhan Ali; Wisudarti, Calcarina Retno; Prasamya, Erlangga (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background: Breast cancer is the most common cancer in woman worldwide. Local Anaesthetic Systemic Toxicity (LAST) is one of the complication in Anesthetic block technique for modified radical mastectomy. Local anesthetic systemic toxicity is rare, but once a LAST occurs, it can be fatal, even if the patient is left untreated. Because of the potential dangers that occur as a result of LAST, an anesthesiologist must understand the mechanism of LAST and good management in handling LAST. Thoracal Paravertebral, Pectoralis I, and Serratus Anterior Plane Block offers complete unilateral block and has long term analgesic effect can be used as an anesthetic technique in Modified Radical Mastectomy. Case Illustration: A 39-year old woman with invasive ductal carcinoma underwent modified radical mastectomy with multiple injection Thoracic paravertebral block (TPVB), Pectoralis 1 (PECS 1), and Serratus Anterior Plane (SAP) Block as a sole anesthesia regiment for this surgery. First anesthetic Peripheral Nerve Block (PNB) is TPVB followed by SAP Block than PECS 1 block. LAST symptom was shown suddenly after the PECS 1 Local Anesthetic (LA) block injection. Previously, repeated aspiration was performed before administering the drug with no blood results. We give Lipid solution to treat the symptom of LAST and the seizure stops within 30 seconds. During surgery, the patient was sedated with titrated dexmedetomidine. Hemodynamic was stable during intraoperative phase. The postoperative pain level is low and there was no complication such as pulmonary and neurological complications.Conclusion: LAST can be performed after Anesthesia block technique. Thoracic paravertebral block, Pectoralis I, and Serratus Anterior Plane Block are enough to covered anestetic and pain management in modified radical mastectomy.